The Influence of Service Quality and Asset Management on Customer Satisfaction in Cafe Businesses in Klepu Village - Gulo, Robin Perdamaian; Maryani, Tri (Mahesa Research Center, 2025)
This study analyzes the effect of service quality and asset management on customer satisfaction at a cafe in Klepu Village, Bergas District, Semarang Regency. Along with the rapid growth of the cafe business, improving service quality and asset management are important factors in increasing customer satisfaction. This study uses a quantitative approach with a survey involving 100 cafe customers selected through a purposive sampling technique. Data analysis was performed using multiple linear regression with SPSS. The results of the study indicate that service quality and asset management simultaneously have a significant effect on customer satisfaction (p < 0.05). Service quality has a greater influence, with a contribution of 60%, while asset management contributes 40%. This finding emphasizes the importance of improving service quality and asset maintenance to improve customer satisfaction and the competitiveness of cafes in the region. This study provides insight for cafe managers in facing competition in the small business sector.